2022
DOI: 10.1029/2022ja030969
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Mercury's Plasma Sheet Horn: Characterization and Contribution to Proton Precipitation

Abstract: The Mercury Surface, Space ENvironment, GEochemistry and Ranging (MESSENGER) spacecraft was the first spacecraft to orbit the planet Mercury. Previous analysis of MESSENGER data has established that of all the planets in the solar system, Mercury's magnetosphere is the most like Earth's, dominated by the Dungey cycle in its dynamic response of the magnetosphere to solar wind forcing. In this work, we identify and describe for the first time Mercury's northern plasma sheet horn—a Dungey cycle feature key to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Observations and simulations have revealed that magnetic reconnection on Mercury's dayside magnetopause enhances solar wind sputtering underneath the cusp (Fatemi et al., 2020; Poh et al., 2016; Raines et al., 2022), which cause enhancement of Na + ‐group ions at high latitudes (Sun, Slavin, et al., 2022). This sputtering effect is expected to also occur on the surface beneath the nightside plasma sheet (Glass et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Observations and simulations have revealed that magnetic reconnection on Mercury's dayside magnetopause enhances solar wind sputtering underneath the cusp (Fatemi et al., 2020; Poh et al., 2016; Raines et al., 2022), which cause enhancement of Na + ‐group ions at high latitudes (Sun, Slavin, et al., 2022). This sputtering effect is expected to also occur on the surface beneath the nightside plasma sheet (Glass et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, solar wind ion sputtering and micrometeroid impact vaporization compete in supplying Mercuryʼs exospheric high-energy particle population with refractory species (e.g., Ca and Mg), while photon-stimulated desorption dominates the supply of energetic volatile and moderately volatile species (i.e., Na, K, and S; Mangano et al 2007;Cassidy et al 2015;Schaible et al 2020;Grava et al 2021;Janches et al 2021). In the same way that fluxes, or precipitation rates, of the particles causing these processes are still in the process of being better constrained (i.e., proton precipitation for solar wind sputtering at Mercury's cusps in Fatemi et al 2020;Glass et al 2022;Raines et al 2022), the understanding of the underlying physics is still a work in progress. At the Moon, precipitation rates seem comparably trivial to compute, but the Moon traveling through Earth's magnetotail and localized crustal fields add complexity to the system (e.g., Lue et al 2011;Poppe et al 2018;Nénon & Poppe 2020).…”
Section: Space Weathering Of Exposed Rocky Surfacesmentioning
confidence: 99%
“…In contrast to the Moon, Mercury's internal magnetic field causes a much more complicated interaction of the planet with the solar wind plasma (Slavin et al., 2008) and prevents impacts on large parts of the hermean dayside surface (Kallio & Janhunen, 2003; Sarantos et al., 2007; Winslow et al., 2014). Instead, precipitation is expected to be more localized on polar cusps at high day side latitudes (Raines et al., 2022), polar horns (Glass et al., 2022), or the night side (Benna et al., 2010). Precipitating ion fluxes are typically lower than the solar wind flux (Fatemi et al., 2020; Glass et al., 2022; Raines et al., 2022; Winslow et al., 2014) and ion energies are expected to vary between significantly smaller than the solar wind ion energy up to several keV (Fatemi et al., 2020; Glass et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, precipitation is expected to be more localized on polar cusps at high day side latitudes (Raines et al., 2022), polar horns (Glass et al., 2022), or the night side (Benna et al., 2010). Precipitating ion fluxes are typically lower than the solar wind flux (Fatemi et al., 2020; Glass et al., 2022; Raines et al., 2022; Winslow et al., 2014) and ion energies are expected to vary between significantly smaller than the solar wind ion energy up to several keV (Fatemi et al., 2020; Glass et al., 2022). Learning more about the surface of Mercury is thus strongly connected to establishing a full understanding of the plasma‐surface interaction to constrain precipitating fluxes of solar wind ions and magnetospheric species.…”
Section: Introductionmentioning
confidence: 99%